Vowel Recognition Revolutionizes Early Childhood Education Globally: Pengenalan Vokal Merevolusi Pendidikan Anak Usia Dini Secara Global - SetiaWati, Dina Candra Eka; Iffatur Rocmah, Luluk (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the challenge of vowel recognition among 3-4-year-old children, focusing on vowels like “e,” “u,” and “o.” Using a Classroom Action Research (CAR) approach, twelve children at KB Aisyiyah 17 Jasem participated in pre-cycle, cycle I, and cycle II interventions. The results showed a significant improvement from a 33.3% recognition rate in the pre-cycle to 95.3% in cycle II, indicating the effectiveness of using ball letter media. This research highlights the importance of tailored teaching methods in enhancing early childhood learning outcomes, particularly in improving vowel recognition skills. Highlight: Tailored CAR approach boosts vowel recognition in early education. Effective ball letter media enhances learning outcomes in young children. Notable 62% increase shows success in improving vowel recognition skills. Keyword: Vowel recognition, Early childhood education, Classroom Action Research, Ball letter media, Learning outcomes